Wear-resistant and weather-resistant coating and preparation method thereof

By using TiO2/MOF composite particles and nano-scale SiO2 composite filler, combined with the photocatalytic nature of MOF, the existing coatings have been solved in terms of weather resistance and degradation efficiency, and the building coating with high weather resistance and high degradation efficiency is achieved, with environmentally friendly characteristics.

CN119859453APending Publication Date: 2025-04-22JIANGSU LANLING POLYMER MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510150160.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing architectural coatings ignore comprehensive performance when pursuing weather resistance, and some components are not environmentally friendly, making it difficult to have high weather resistance and high degradation efficiency at the same time.

Method used

TiO2/MOF composite particles and nano-scale SiO2 composite filler are used, and MOF is coated outside TiO2 to enhance the resistance to ultraviolet light, and the weather resistance and density of the coating are improved through the synergistic action of TiO2 and SiO2, while the photocatalytic degradation of harmful substances is used.

Benefits of technology

It achieves high weather resistance and high degradation efficiency of the coating, improves the hardness and density of the coating, and has environmentally friendly characteristics, which can effectively degrade harmful substances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005267829460000011
    Figure BDA0005267829460000011
  • Figure BDA0005267829460000021
    Figure BDA0005267829460000021
  • Figure BDA0005267829460000051
    Figure BDA0005267829460000051
Patent Text Reader

Abstract

The invention relates to the field of coatings, in particular to a wear-resistant and weather-resistant coating and a preparation method thereof. The resin composition comprises the following components in parts by weight: 80-120 parts of a resin mixture; 5 to 12 parts of isocyanate; 4 to 10 parts of polydimethylsiloxane; 1-3 parts of sodium silicate; 6 to 10 parts of TiO2 / MOF composite particles; 2 to 4 parts of nanoscale SiO2; 2-4 parts of a fluorine monomer; 5-10 parts of an auxiliary agent; according to the coating, TiO2 / MOF composite particles and nanoscale SiO2 are adopted for compounding filler, TiO2 is coated with MOF, the ultraviolet light resistance of the coating is enhanced while the performance of TiO2 is reserved, meanwhile, MOF can adsorb SiO2, TiO2 can be matched with SiO2 to enhance the weather resistance of the coating, and TiO2 can serve as a photocatalyst to degrade harmful substances; the compound filler is cooperated with sodium silicate, so that the roughness and hardness of the coating are further improved, and the compactness and hardness of the coating are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, and in particular to a wear-resistant and weather-resistant coating and a preparation method thereof. Background Art

[0002] With the rapid development of the construction industry, people's requirements for building materials are also increasing. As an important part of the external protective layer of buildings, the performance of architectural coatings directly affects the service life and aesthetics of buildings. Especially in environments with strong ultraviolet rays and changeable climates, the weather resistance of coatings is particularly important. There are many weather-resistant coatings in existing coatings. However, these coatings ignore the comprehensive performance of coatings while pursuing weather resistance, and the components added to some coatings are not environmentally friendly. At present, green sustainability will become the mainstream of future technological development. Various motor vehicle exhaust treatment plans have been proposed in various places to alleviate urban air pollution. Researchers have also begun to study architectural coatings with environmentally friendly ingredients that can help alleviate urban air pollution. The current architectural coatings have poor comprehensive performance. The degradation efficiency of coatings that pursue high weather resistance is low, while the coatings that pursue high degradation efficiency cannot have high weather resistance. Therefore, there is an urgent need for a coating with excellent comprehensive performance, both weather resistance and high degradation efficiency. Summary of the invention

[0003] The purpose of the present invention is to provide a wear-resistant and weather-resistant coating and a preparation method thereof in view of the deficiencies in the prior art.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] The first aspect of the present invention is to provide a wear-resistant and weather-resistant coating, which comprises, by weight:

[0006]

[0007]

[0008] Preferably, the resin mixture comprises at least one of siloxane-modified epoxy resin, silicone acrylate, and epoxy-modified silicone resin.

[0009] Preferably, the TiO2 / MOF composite particles are of a core-shell structure, wherein MOF is coated on the outside of TiO2.

[0010] Preferably, the particle size of the nano-scale SiO2 is 7-40 nm.

[0011] Preferably, the auxiliary agent includes at least one of a diluent, a defoaming agent, a curing agent, a leveling agent, a wetting agent, and an antioxidant.

[0012] The second aspect of the present invention is to provide a method for preparing the above-mentioned wear-resistant and weather-resistant coating, the steps comprising:

[0013] S1, weighing TiO2 / MOF composite particles and nano-SiO2 in parts by weight to prepare a TiO2 / MOF dispersion and a nano-SiO2 dispersion, mixing the TiO2 / MOF dispersion and the nano-SiO2 dispersion, and then sequentially subjecting the mixture to ball milling and ultrasonic treatment to obtain a filler dispersion;

[0014] S2, weighing the resin mixture, polydimethylsiloxane, isocyanate and fluorine monomer in parts by weight, mixing at room temperature, adding the filler dispersion while stirring, and then heating to react, so as to obtain a resin mixture;

[0015] S3. Weigh sodium silicate and auxiliary agents in parts by weight, add them to the resin mixture, stir them thoroughly and then perform vacuum degassing treatment to obtain the wear-resistant and weather-resistant coating.

[0016] Preferably, in step S1, the preparation step of the TiO2 / MOF composite particles comprises:

[0017] A1. After drying the nano-TiO2 particles, disperse them in ethanol, add 3-aminopropyltriethoxysilane, and sequentially perform stirring treatment, ultrasonic treatment and centrifugation treatment, take the precipitate, dry and grind it, and obtain modified nano-TiO2 particles;

[0018] A2, placing the MOF material in a silane coupling agent for surface treatment, washing, drying and grinding the material, and then dispersing the MOF particles in butyl acetate to prepare a MOF dispersion;

[0019] A3. Add the modified nano-TiO2 particles to the MOF dispersion, perform ultrasonic treatment and suction filtration in sequence, and then dry, calcine and grind the precipitate to obtain the TiO2 / MOF composite particles.

[0020] More preferably, in step A1, the nano-TiO2 particles are composite particles obtained by mixing and calcining melamine and TiO2.

[0021] Preferably, in step S2, the temperature-raising reaction comprises: firstly raising the temperature to 75-85°C at a rate of 3-5°C / min for reaction for 1-2h, and then raising the temperature to 130-165°C at a rate of 6-8°C / min for reaction for 3-5h.

[0022] Preferably, in step S3, the vacuum degassing treatment is performed for 10-30 minutes.

[0023] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:

[0024] The coating of the present invention adopts TiO2 / MOF composite particles and nano-scale SiO2 compound filler. MOF is coated on the outside of TiO2, which retains the performance of TiO2 while enhancing the coating's resistance to ultraviolet light. At the same time, MOF can adsorb SiO2, so that TiO2 can not only cooperate with SiO2 to enhance the weather resistance of the coating, but also act as a photocatalyst to degrade harmful substances. The compound filler cooperates with sodium silicate to further improve the roughness and hardness of the coating, thereby improving the density and hardness of the coating. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0027] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.

[0028] Example 1

[0029] This embodiment provides a method for preparing a wear-resistant and weather-resistant coating, the steps comprising:

[0030] S1. Weigh 10 parts of TiO2 / MOF composite particles and 4 parts of nano-SiO2 by weight to prepare a TiO2 / MOF dispersion and a nano-SiO2 dispersion, mix the TiO2 / MOF dispersion and the nano-SiO2 dispersion, and then perform ball milling and ultrasonic treatment in sequence to obtain a filler dispersion;

[0031] The steps for preparing the TiO2 / MOF composite particles include:

[0032] A1. Mix melamine and TiO2 (melamine:TiO2=1:2) and calcine to obtain nano-TiO2 particles. After drying the nano-TiO2 particles, disperse them in ethanol, add 3-aminopropyltriethoxysilane, and perform stirring treatment, ultrasonic treatment and centrifugation treatment in sequence. Take the precipitate and dry and grind it to obtain modified nano-TiO2 particles.

[0033] A2, placing the MOF material in a silane coupling agent for surface treatment, washing, drying and grinding the material, and then dispersing the MOF particles in butyl acetate to prepare a MOF dispersion;

[0034] A3, adding the modified nano-TiO2 particles to the MOF dispersion, performing ultrasonic treatment and suction filtration treatment in sequence, and then drying, calcining and grinding the precipitate to obtain the TiO2 / MOF composite particles;

[0035] S2. Weigh 50 parts of siloxane-modified epoxy resin, 50 parts of silicone acrylate, 4 parts of polydimethylsiloxane, 6 parts of isocyanate and 2 parts of fluorine monomer by weight, mix at room temperature and add the filler dispersion while stirring, first heat to 75°C at a rate of 3°C / min for reaction for 2h, then heat to 165°C at a rate of 8°C / min for reaction for 3h to obtain a resin mixture;

[0036] S3. Weigh 3 parts of sodium silicate, 1 part of diluent, 2 parts of curing agent and 2 parts of antioxidant by weight, add them to the resin mixture, stir thoroughly and perform vacuum degassing treatment for 20 minutes to obtain the wear-resistant and weather-resistant coating.

[0037] Example 2

[0038] This embodiment provides another method for preparing a wear-resistant and weather-resistant coating, the steps comprising:

[0039] S1. Weigh 7 parts of TiO2 / MOF composite particles and 3 parts of nano-SiO2 by weight to prepare a TiO2 / MOF dispersion and a nano-SiO2 dispersion, mix the TiO2 / MOF dispersion and the nano-SiO2 dispersion, and then perform ball milling and ultrasonic treatment in sequence to obtain a filler dispersion;

[0040] Wherein, the preparation steps of the TiO2 / MOF composite particles are the same as those in Example 1;

[0041] S2. Weigh 100 parts of epoxy-modified silicone resin, 8 parts of polydimethylsiloxane, 10 parts of isocyanate and 4 parts of fluorine monomer by weight, mix at room temperature and add the filler dispersion while stirring, first heat to 75°C at a rate of 5°C / min to react for 2h, then heat to 150°C at a rate of 6°C / min to react for 3h to obtain a resin mixture;

[0042] S3. Weigh 3 parts of sodium silicate, 2 parts of curing agent, 2 parts of antioxidant, 1 part of defoaming agent and 2 parts of wetting agent by weight, add them to the resin mixture, stir thoroughly and perform vacuum defoaming treatment for 10 minutes to obtain the wear-resistant and weather-resistant coating.

[0043] Comparative Example 1

[0044] This comparative example provides a method for preparing a coating, which does not include step S1 of embodiment 1, and replaces the filler dispersion in step S2 of embodiment 1 with conventional TiO2 particles, and the rest is the same as embodiment 1.

[0045] Comparative Example 2

[0046] This comparative example provides another method for preparing a coating, wherein no vacuum degassing treatment is performed in step S3, and the rest is the same as in Example 1.

[0047] Comparative Example 3

[0048] This comparative example provides another method for preparing a coating, wherein polydimethylsiloxane, isocyanate and fluorine monomer are not added in step S2, sodium silicate is not added in step S3, and the rest are the same as in Example 1.

[0049] Detection Example

[0050] The coatings prepared by the preparation methods described in Examples 1-2 and Comparative Examples 1-3 were tested for performance, and the specific testing standards are as follows:

[0051] Test the adhesion of the coating by pull-off method according to GB / T 5210-2006;

[0052] Test the pencil hardness of the coating according to GB / T 6739-2022;

[0053] Test the impact resistance of the coating according to GB / T 1733-2020;

[0054] Test NO2 degradation performance according to GB / T39716-2020

[0055] Ultraviolet accelerated aging test: Expose the coating sample to ultraviolet rays, use a colorimeter to measure the color change of the coating sample before and after exposure (the smaller the ΔE, the less obvious the color change), and use a tensile testing machine to perform a tensile test on the coating sample to measure its tensile strength;

[0056] The test results are shown in Table 1;

[0057] Table 1

[0058]

[0059] As shown in Table 1, compared with Example 1, Comparative Example 1 uses conventional TiO2 as a filler, and the color change value is significantly increased, the hardness is reduced, the adhesion is poor, and the NO2 degradation rate is also significantly reduced. This is because conventional TiO2 is used alone as a filler in the coating, and the degree of crosslinking with other components is low, so that its performance cannot be fully exerted. The present invention compounds it with MOF to improve the degree of crosslinking between the components. It can be seen that the composite filler of the present invention can significantly improve the weather resistance and wear resistance of the coating while allowing TiO2 to fully exert its photocatalytic properties, thereby improving the NO2 degradation rate; Comparative Example 2 did not perform vacuum degassing treatment, resulting in bubbles in the coating affecting the density of the coating, thereby reducing the adhesion of the coating; Comparative Example 3 only improves the coating performance by compounding fillers, lacks synergy with other materials, thereby affecting the various properties of the coating.

[0060] In summary, the coating of the present invention adopts TiO2 / MOF composite particles and nano-scale SiO2 compound filler. MOF is coated on the outside of TiO2, which retains the performance of TiO2 while enhancing the coating's resistance to ultraviolet light. At the same time, MOF can adsorb SiO2, so that TiO2 can not only cooperate with SiO2 to enhance the weather resistance of the coating, but also act as a photocatalyst to degrade harmful substances; the compound filler cooperates with sodium silicate to further improve the roughness and hardness of the coating, thereby improving the density and hardness of the coating.

[0061] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.

Claims

1. A wear-resistant and weather-resistant coating, characterized in that: By weight, the components include:

2. The wear-resistant and weather-resistant coating according to claim 1, characterized in that: The resin mixture comprises at least one of siloxane-modified epoxy resin, silicone acrylate and epoxy-modified silicone resin.

3. The wear-resistant and weather-resistant coating according to claim 1, characterized in that: The TiO2 / MOF composite particles are of a core-shell structure, wherein MOF is coated on the outside of TiO2.

4. The wear-resistant and weather-resistant coating according to claim 1, characterized in that: The particle size of the nano-scale SiO2 is 7-40nm.

5. The wear-resistant and weather-resistant coating according to claim 1, characterized in that: The auxiliary agent includes at least one of a diluent, a defoamer, a curing agent, a leveling agent, a wetting agent, and an antioxidant.

6. A method for preparing the wear-resistant and weather-resistant coating according to any one of claims 1 to 5, characterized in that the steps include: S1, weighing TiO2 / MOF composite particles and nano-SiO2 in parts by weight to prepare a TiO2 / MOF dispersion and a nano-SiO2 dispersion, mixing the TiO2 / MOF dispersion and the nano-SiO2 dispersion, and then sequentially subjecting the mixture to ball milling and ultrasonic treatment to obtain a filler dispersion; S2, weighing the resin mixture, polydimethylsiloxane, isocyanate and fluorine monomer in parts by weight, mixing at room temperature, adding the filler dispersion while stirring, and then heating to react, so as to obtain a resin mixture; S3. Weigh sodium silicate and additives in parts by weight, add them to the resin mixture, stir them thoroughly and then perform vacuum degassing treatment to obtain the wear-resistant and weather-resistant coating.

7. The preparation method according to claim 6, characterized in that: In step S1, the preparation steps of the TiO2 / MOF composite particles include: A1. After drying the nano-TiO2 particles, disperse them in ethanol, add 3-aminopropyltriethoxysilane, and sequentially perform stirring treatment, ultrasonic treatment and centrifugation treatment, take the precipitate, dry and grind it, and obtain modified nano-TiO2 particles; A2, placing the MOF material in a silane coupling agent for surface treatment, washing, drying and grinding the material, and then dispersing the MOF particles in butyl acetate to prepare a MOF dispersion; A3. Add the modified nano-TiO2 particles to the MOF dispersion, perform ultrasonic treatment and suction filtration in sequence, and then dry, calcine and grind the precipitate to obtain the TiO2 / MOF composite particles.

8. The preparation method according to claim 7, characterized in that: In step A1, the nano-TiO2 particles are composite particles obtained by mixing melamine and TiO2 and calcining them.

9. The preparation method according to claim 6, characterized in that: In step S2, the temperature-raising reaction comprises: firstly heating the temperature to 75-85°C at a rate of 3-5°C / min and reacting for 1-2h, and then heating the temperature to 130-165°C at a rate of 6-8°C / min and reacting for 3-5h.

10. The preparation method according to claim 6, characterized in that: In step S3, the vacuum degassing treatment lasts for 10-30 minutes.